Pengaruh Penggunaan Media Digital Terhadap Prestasi Belajar IPS Siswa SD Swakarya - Yusnaldi, Eka; Pebri, Mitta; Nabila, Putri; Hasibuan, Najwa Naumira; Salsabila, Maya; Hasibuan, Salsa Bila (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze the effect of using digital media on students' Social Sciences (IPS) learning achievement at SD Swakarya. The method used in this research was an experiment with a pretest-posttest control group design. The research sample consisted of an experimental group that used digital media in social studies learning and a control group that used conventional methods. Learning achievement data is collected through validated and reliable learning outcome tests. Data analysis was carried out using the t test to see significant differences between the two groups. The research results show that there is a significant increase in the social studies learning achievement of students who use digital media compared to students who use conventional methods. These findings indicate that the use of digital media can be an effective alternative in improving students' social studies learning achievement. The implication of this research is the need to integrate digital media in the learning curriculum in elementary schools to maximize student learning potential